Rancang Bangun Sistem Kontrol dan Monitoring Suhu dan Kelembaban Tanah pada Greenhouse berbasis Internet of Thing menggunakan Aplikasi Telegram - Pramartaningthyas, Ellys Kumala; Ma'shumah, Siti; Mahmudah, Ratna Sri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2023)
The quality of plant growth is significantly influenced by environmental factors, including temperature, air humidity, soil moisture, light intensity, and air quality. Therefore, an agrotechnology approach is required to manage exposure to these environmental factors in accordance with the needs of plant growth processes, which can be achieved through greenhouse technology. To facilitate real-time and remote monitoring and control in the greenhouse farming system, this research involves the design of a temperature and humidity control and monitoring system based on the Internet of Things (IoT). This study employed a NodeMCU ESP8266 microcontroller and a DHT11 sensor to detect the temperature and humidity levels in the greenhouse. The performance test results show that the system works well according to the programming algorithm provided, with an average error rate of 1.2% for the temperature sensor and 1.17% for the humidity sensor. The test results for notification delay time on the Telegram application also meet the standard requirements of Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON), with an average delay value of 0.532882 ms